Relationship between social support, life satisfaction and subjective well-being in brazilian adolescents - Castellá Sarriera, Jorge (2015)
This study explores the subjective well-being, overall life satisfaction and perceived social support of Brazilian adolescents by analysing different models that explain the relationships among these three constructs. The sample is comprised of 1,588 adolescents (aged 12–16, 65.5% female), who answered the Personal Well-Being Index (PWI), a measure of Perceived Social Support of Family and Friends, and also an Overall Life Satisfaction single-item scale (OLS). MANOVA and ANOVA were used to assess the differences between groups, with respect to gender, it is observed that girls present lower means than boys for the OLS. Considering age, there was a significant decrease in the mean of the PWI with age. Boys present lower means of friends’ social support. Structural Equation Modelling was used to test theoretical frameworks on data. After analysing different models, the best fit model is presented using the PWI as a mediating factor between social support and satisfaction with life. The perception of social support from family and friends results to be a significant dimension of well-being among Brazilian adolescents. The importance of social support for the subjective well-being is explained by identifying how it contributes to the overall life satisfaction of adolescents.